Writing for Publication - Jalongo, Mary Renck; Saracho, Olivia N. (Springer, 2016)
A group of higher education faculty members from different colleges and departments were participating in a 3-day professional development institute on writing for professional publication. The pressure to publish was on at their institution, newly categorized as a university. Prior to the mid-morning break on the fi rst day, the presenter asked the participants to write their concerns about publishing on Post-it notes and then read and categorized them before the group reconvened. The great majority of the participants were worried about their ability to fulfi ll the escalating expectations for faculty. Only a few had published previously and they wondered if they were capable of writing well enough to publish their work. As a way to allay their fears, the presenter offered to assess a short writing sample from each participant that evening and return it the next day. They had the choice of composing something during the afternoon, or they could submit just a few pages from an unpublished manuscript. The next morning, she announced, “Good news. All of you have achieved a level of skill that is suffi cient to get you published.” The group’s response was relieved laughter and some skeptical looks so, while returning the papers with her written comments she said, “You realize, of course, that there is a huge selective bias operating in my favor here. All of you have graduate degrees and nearly all have doctorates. It’s doubtful that anyone could earn those degrees without solid writing skills. Plus, all of you volunteered to take 3 days out of your busy schedule to learn about writing for publication. This suggests that you are seeking out opportunities to learn or, at the very least, that you respond to helpful nudging from colleagues. You also were candid about your concerns and decided to meet the challenges of writing together. All of this bodes well for a successful outcome. I will do my absolute best to help you.”
Transitions and Tools that Support Scholars’ Success